Kajian Kesesuaian Dan Daya Dukung Kawasan Wisata Danau Pading Kabupaten Bangka Tengah Provinsi Bangka Belitung - Br sitepu, Agry rut Benaya; Supratman, Okto; Aisyah, Siti; Okto Supratman (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2023)
Agry Rut Benaya Br Sitepu (2021811017) Study of the Suitability and Carrying Capacity of the Lake Pading Tourism Area, Central Bangka Regency, Bangka Belitung Province. (Supervisors: Okto Supratman and Siti Aisyah) Pading Lake Tourism is still relatively called new and its beauty has been developed as a tourist attraction considering the condition of the surrounding environment which offers natural beauty and serenity with great potential for spread. Views of the lake and hills can add to the comfort of every tourist. Tourist activities that can be carried out by tourists are picnic activities, relaxing, playing in the water, and boating around the lake. Through this study, it is hoped that it can increase the carrying capacity of the community for the natural beauty and comfort of the Pading Lake tourist destination in Perlang Village. The method used in determining station points is to conduct field surveys, by taking several environmental parameters such as depth, brightness, lakeside width, slope, current speed to determine the tourism suitability index, and the carrying capacity of the Pading Lake tourism area. The results of the tourism suitability index study obtained the value of the camping category by 85%, the Boat category by 92%, the Relax Sitting category by 69%, the Outbound category by 83%, the Swimming category by 78%. The carrying capacity of the area in the Camping category is 234 people/day, the Boat category is 792 people/day, the Sitting Relax category is 655 people/day, the Outbound category is 487 people/day, the swimming category is 172 people/day. Keywords: Pading Lake Tourism, Compatibility, Regional Carrying Capacity